The future of competition co-creating unique value with customers - Prahalad, C. K.; Ramaswamy, Venkatram (Boston, Mass. : Harvard Business School Pub., 2004)
"Based on a wide range of ongoing experimentation in co-creation across many industries, The Future of Competition presents a new approach to value creation. In this framework, consumer-company interactions and personalized co-creation experiences - enabled by technical and social infrastructures - allow each consumer to co-create unique value with a network of companies and consumer communities." "Using vivid examples of companies that are discovering next practices, Prahalad and Ramaswamy discuss the key building blocks of co-creation - dialogue, access, risk assessment, and transparency (DART) - and explore how new experience technologies and social capabilities can enable robust experience environments."--Jacket.
The co-creation of value -- Building blocks of co-creation -- The co-creation experience -- Experience innovation -- Experience personalization -- Experience networks -- The market as a forum -- Creating new strategic capital -- Manager as consumer -- Rapid knowledge creation -- Strategy as discovery -- Building new capabilities for the future.
Includes bibliographical references (pages 239-250) and index.
Description based on print version record.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Competition; Customer relations; Customer services; Strategic planning; Economic value added; Success in business; Compétitivité (Économie); Relations avec la clientèle; Service à la clientèle; Planification stratégique; Valeur économique ajoutée; Succès dans les affaires; Concurrence; Service à la clientèle; Politique de l'entreprise.; Relations commerciales; Comportement du consommateur; Doctrines économiques; Competition; Customer relations; Customer services; Economic value added; Strategic planning; Success in business; Economische waarde; Strategische planning; Cliënten; Gewinnmaximierung; Kundenbetreuung; Kundenmanagement; Kundenorientierung; Strategische Planung; Wertschöpfung; Wettbewerbsstrategie; Contatos com clientes; Serviço ao cliente; Planejamento estratégico; Réussite dans les affaires; Création de valeur; Valeur ajoutée; Planification stratégique; Service à la clientèle; Relation avec la clientèle; Concurrence; Wettbewerb; Strategisches Management; Cliënten; Concurrence; Contatos com clientes; Création de valeur; Economische waarde; Planejamento estratégico; Relation avec la clientèle; Réussite dans les affaires; Serviço ao cliente; Strategische planning; Valeur ajoutée; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science